Hemolytic disease of the fetus and newborn and Rhesus alloimmunization in Latin American countries: a scoping review - Mário Dias Corrêa Júnior; Salvador Espino y Sosa; Milene Fernandes; Lais do Carmo; Renato Watanabe de Oliveira; Gabriela Kanevsky (BMC Pregnancy and Childbirth)
Abstract Background Hemolytic disease of the fetus and newborn (HDFN) is a condition due to maternal blood group antibodies targeting antigens in fetal red blood cells, with significant prenatal/perinatal morbidity and mortality. Severe HDFN cases are often associated with alloimmunization against Rhesus D (RhD) or Kell antigens. Information about HDFN epidemiology and treatment in Latin American countries is limited. This review aims to identify and synthesize the available evidence on the epidemiology and management of HDFN in this region. Methods In July 2023, EMBASE, PubMed, LILACS, and other databases were searched for articles reporting epidemiology, treatment, prenatal and perinatal outcomes, and patient journey of HDFN cases in Latin American countries. A snowball search of cross-references and gray literature complemented the initial search. Publications in English, Spanish, and Portuguese were reviewed. Data were extracted using a defined template and charted in tables. Results We reviewed five guidelines and 19 observational studies from Brazil, Chile, Mexico, Argentina, Colombia, Panamá, Paraguay, and Peru. HDFN due to Rh alloimmunization ranged from 0.5 to 5 per 1000 live births, and anti-D remains the most frequent alloantibody type for severe HDFN. The perinatal mortality rate of HDFN is approximately 1.3–1.6 per 100,000 live births, and fetal deaths can reach 30% among patients treated with intrauterine transfusions. Up to 47% of alloimmunized pregnancies were referred to reference centers only during the third trimester. About 60% of eligible pregnancies received anti-D IgG prophylaxis. Conclusions Although estimates in LATAM countries are scarce and lack standardized measures, we observed that the incidence, morbidity, and mortality of HDFN in this region are problematic. RhD alloimmunization was reported in approximately up to 70% of severe HDFN cases, despite anti D HDFN being largely preventable.